How Far Did I Throw It?

A body is thrown horizontally with velocity 2 g h \sqrt {2gh} from the top of a tower of height h h . It strikes the level ground at a distance of x x from the tower. The value of x x is __________ . \text{\_\_\_\_\_\_\_\_\_\_}.

h 2 \frac{h}{2} 2 h 3 \frac{2h}{3} h h 2 h 2h

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Akhil Bansal
Jan 16, 2016

Applying Newton's equation, s = u t + 1 2 a t 2 s = ut + \dfrac{1}{2}at^2 in horizontal and vertical direction.
In horizontal Direction , x = t 2 g h + 0 . . 1 \large x = t\sqrt{2gh} + 0 \quad \quad \quad .. \boxed{1} In vertical direction , h = 1 2 g t 2 . . 2 \large h = \dfrac{1}{2}gt^2 \quad \quad \quad \quad ..\boxed{2} Substituting value of t from 2 \boxed{2} in 1 \boxed{1} ,
x = 2 g h × 2 h g \large x = \sqrt{\dfrac{2gh \times 2h}{g}} x = 2 h \large \boxed{\color{#3D99F6}{x = 2h}}

Prokash Shakkhar
Dec 15, 2016

There is a very important point is that the projectile has thrown parallel to X a x i s \color{#D61F06}{X-axis} . So the vertical component v 0 s i n θ = v 0 s i n 0 = 0 v_0 sin\theta = v_0 sin 0^\circ = 0 ..Now, h = v 0 s i n θ t + 1 2 g t 2 h= v_0 sin \theta t +\frac{1}{2} g t^2 h = 1 2 g t 2 \Rightarrow h=\frac{1}{2} g t^2 t = 2 h g \Rightarrow t= \sqrt{\frac{2h}{g}} Then the time came to find out the distance traveled on X a x i s \color{#D61F06}{X -axis} .. As this component is constant always, We can use the formula of uniform velocity. Then the equation forms, x = v 0 t x =v_0 t x = 2 g h 2 h g \Rightarrow x= \sqrt{2gh * \frac{2h}{g}} x = 2 h \Rightarrow \boxed{\color{#E81990}{x= 2h}}

Munem Shahriar
Mar 20, 2018

We know that,

  • x = v t . . . ( 1 ) x = vt~~~~ ...(1) where x x is the distance.

  • h = u t + 1 2 g t 2 . . . . ( 2 ) h = ut+ \dfrac 12 gt^2~~~~ ....(2) where u = 0. u = 0.

We have v = 2 g h , v = \sqrt{2gh}, now from ( 1 ) : (1):

x = v t x = 2 g h t x 2 g h = t . x = vt \\ x = \sqrt{2gh} \cdot t \implies \dfrac x{\sqrt{2gh}} = t.

Substituting the value of t t in ( 2 ) : (2):

h = g 2 ( x 2 g h ) 2 h = g 2 ( x 2 2 g h ) h = g x 2 4 g h h = x 2 4 h 4 h 2 = x 2 x = 2 h \begin{aligned} h & = \dfrac g2\left(\dfrac x{\sqrt{2gh}}\right)^2 \\ h& = \dfrac g2\left(\dfrac {x^2}{2gh}\right) \\ h & = \dfrac{gx^2}{4gh} \\ h& = \dfrac{x^2}{4h} \\ 4h^2 &= x^2\\ \implies x & = \boxed{2h} \\ \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...